Utilização de técnicas de otimização em redes de abastecimento de água - Pires, Rubem (1979)
The objective of this study was to analize the optimization tecniques for the main line and the distribution network of an urban water supply system. In the distribution subsystem, it was considered a branched network and a closed-loop network. According to the selected model, it was used mathematical optimization (Calculus, linear programming) or simulation. For each system, the traditional method were analyzed and the proposed method were also applied and the results were compared. The application of the methodologies were for the projected systems of Ponta de Pedras and Igarapé-Mirim in state of Pará, Brazil. The results obtained were discussed detailed.